Walkability and business performance of brick-and-mortar retail stores in the Central Business District of Tacloban City - Ala, Kristelle Cheska Bella M.; Ala, Kristelle Cheska Bella M.; Babon, Lance Neil A.; Borgueta, Sachi Mari C.; Cagara, Richard V.; Oledan, Ivan Gil G. (Tacloban City Division of Management, University of the Philippines Tacloban College, 2025)
This mixed-methods study explored the relationship between walkability and the business performance of brick-and-mortar retail stores in Tacloban City's Central Business District (CBD). Using the Global Walkability Index (GWI), field surveys evaluated safety, security, convenience, and attractiveness, showing a rise in walkability scores from 55 (2015) to 75 (2025). Surveys of business owners and managers revealed moderate business performance, particularly among micro-enterprises. Statistical analysis showed a weak positive correlation between GWI and business performance (Kendall's Tau - 0.354), though the result was not statistically significant (p=0.199). Qualitative insights and policy analysis suggested that improving walkability through pedestrian infrastructure investment, disaster-resilient urban planning, and stricter building code enforcement could boost commercial vitality. The study recommended technology-enhanced urban design and public education campaigns to create safer, more inclusive, and economically vibrant pedestrian environments.
Undergraduate thesis (B.S. Management) -- University of the Philippines, Tacloban.
Includes bibliographical references.
Keywords: Walkability -- Philippines -- Tacloban City; Walkability; Business performance; Brick and mortar retail stores; Central business district (CBD).; Global walkability index (GWI).